A direct evidence of solute interactions with a moving ferrite/austenite interface in a model Fe-C-Mn alloy. (August 2016) - Danoix, F.; Sauvage, X.; Huin, D.; Germain, L.; Gouné, M.
Abstract: The coupled-solute drag during ferrite growth in steels is widely discussed in the literature and remains still controversial since little direct evidences were adduced to support this effect. In this paper, from a correlative microscopy approach, a selected migrating ferrite/austenite interface in a model FeMnC alloy is quantitatively analysed by atom probe tomography and Energy Dispersive X-Ray Spectroscopy at the nanoscale. They show unambiguously a strong co-segregation of both carbon and manganese at the interface during ferrite growth at 680 °C. The obtained results support the coupled-solute drag effect as an operating mechanism during ferrite growth. Graphical abstract: